Agricultural support to combat AIDS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Dr Grace Malindi, Deputy Director of the Department of Agriculture Extension Services in Malawi, describes a variety of programmes that are supporting communities affected by AIDS.